Frontier Language Models on GPQA Diamond and Reasoning Benchmarks v9 Performance - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: Which frontier language models achieve highest scores on GPQA Diamond Humanity Last Exam and difficult reasoning benchmarks v9. 12 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.2/10. This report is a machine-generated literature synthesis and does not constitute orig
Machine-generated literature synthesis.